Neurobehavioral and biochemical changes in Nauphoeta cinerea following dietary exposure to chlorpyrifos (2016)
The present study aimed to increase our understanding about the mode of toxic action of organophosphate pesticides in insects by evaluating the biochemical and neurobehavioral characteristics in Nauphoeta cinerea exposed to chlorpyrifos (CPF)-contaminated diet. The insects were exposed for 35 consecutive days to CPF at 0.078, 0.15625, 0.3125 and 0.625 μg/g feed. Locomotor behavior was assessed for a 10-min trial in a novel arena and subsequently, biochemical analyses were carried out using the cockroaches’ heads. In comparison to control, CPF-exposed cockroaches showed significant decreases in the total distance traveled, body rotation, turn angle and meandering, along with significant increase in the number of falls, time and episodes of immobility. The marked decrease in the exploratory profiles of CPF-exposed cockroaches was confirmed by track plots, whereas occupancy plot analyses showed a progressive dispersion at 0.15625 μg/g feed group. Moreover, the heads of CPF-exposed cockroaches showed marked decrease in acetylcholinesterase activity and antioxidant status with concomitant significant elevation in dichlorofluorescein oxidation and lipid peroxidation levels in CPF-treated cockroaches. Gas Chromatography–Mass Spectrometry analyses revealed bioaccumulation of CPF in cockroaches exposed to concentrations above 0.078 μg/g feed. The findings from this investigation showed N. cinerea as a value model organism for the risk assessment of environmental organophosphate contamination in insects.